2008
DOI: 10.1111/j.1574-6968.2008.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with ectomycorrhizas of slash pine (Pinus elliottii) in south-eastern Queensland, Australia

Abstract: Bacterial communities associated with ectomycorrhizal and uncolonized roots of Pinus elliottii (slash pine) collected from a plantation in south-east Queensland, Australia, were investigated, using cultivation-dependent and -independent methods. Denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA gene PCR products obtained using a cultivation-independent approach revealed that bacterial communities associated with ectomycorrhizal root tips differed significantly from those associated with roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
2
19
1
Order By: Relevance
“…This number is higher than what have been found in previous studies on bacteria associated with EcM, using HTS2345, T-RFLP27, RFLP9 and DGGE analysis9. Several of the bacterial phyla detected in our study are known to be relatively abundant and ubiquitous in soil, such as Acidobacteria, Actinobacteria, Bacteroidetes, Proteobacteria and Verrucomicrobia4647.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…This number is higher than what have been found in previous studies on bacteria associated with EcM, using HTS2345, T-RFLP27, RFLP9 and DGGE analysis9. Several of the bacterial phyla detected in our study are known to be relatively abundant and ubiquitous in soil, such as Acidobacteria, Actinobacteria, Bacteroidetes, Proteobacteria and Verrucomicrobia4647.…”
Section: Discussioncontrasting
confidence: 73%
“…Multiple well-known symbioses harbor rich and diverse bacterial populations. These include lichens127, fungal endophytes8, as well as mycorrhizal fungi910111213.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several Pseudomonas and Burkholderia spp. were found to be associated with fungal hyphae, probably growing on fungal exudates (Singh and Arora, 2001;De Boer et al, 2005;Izumi et al, 2008). The fact that the numbers of bacteria belonging to these genera did not increase upon introduction of Absidia hyphae makes it unlikely that the growth response of collimonads was due to the assimilation of exudates.…”
Section: Discussionmentioning
confidence: 91%
“…They revealed that the bacterial communities colonizing the ectomycorrhizal roots differed from those of uncolonized roots and that the ectomycorrhizal species differentially impacted the structure of ectomycorrhizosphere bacterial communities (2,11,12,22,35,37). One mycorrhizal species could be colonized by either very similar or contrastingly different bacterial communities (2,11,13).…”
mentioning
confidence: 96%